Considering Local Integration for Refugees in Indonesia - Olivia, Yessi; Nizmi, Yusnarida Eka; Jamaan, Ahmad; Iskandar, Irwan; Saeri, Mohammad; Deanty, Haniva Sekar (Universitas Muhammadiyah Yogyakarta, 2020)
This study discusses refugees who have been stranded in a transit country for years. These protracted refugees have to deal with a reality that the chance of getting resettlement in a third country has become slim, and the option of returning to their country of origin will only jeopardize their lives. Indonesia is not a state party to the 1951 Refugee Convention that lays a responsibility to assimilate refugees in the resettlement countries. Indonesia, however, has opened its door for refugees based on humanity’s solidarity and the fact that Indonesia’s legal framework on human rights acknowledges the right to seek asylum in other countries and abides by the non-refoulement principle. The situation has become problematic when the number of refugees coming to Indonesia has continued to increase, but Indonesia does not have a comprehensive refugee policy to support them. By looking at the case of refugees living in Pekanbaru, this study concludes that Indonesia should consider the local integration option as one of the viable solution to the protracted refugee situations in Indonesia.